(untitled) (Journal Edutama Multidisciplinary Indonesian, 2025)
Teacher integrity is one of the key factors in creating a healthy and quality educational environment, especially at the basic education level. The teacher’s professional code of ethics and the application of legal discipline have an important role in maintaining and improving this integrity. The teacher’s professional code of ethics functions as a moral and professional guideline for teachers in implementing it, ensuring that they act in accordance with established values, such as honesty, responsibility and discipline. Meanwhile, disciplinary punishment is a tool to enforce rules and provide consequences for violations committed by teachers, both related to professional behavior and ethics in their work. This aims to analyze the role of codes of ethics and disciplinary punishment in maintaining the integrity of elementary school teachers. The research results show that implementing a clear code of ethics and good understanding among teachers can prevent violations and strengthen commitment to professionalism. Meanwhile, disciplinary punishment that is applied fairly and in accordance with the violations committed can be an effective correction mechanism, restore teacher integrity, and create a more conducive educational environment. Thus, both elements of the code of ethics and punitive discipline play a synergistic role in ensuring that elementary school teachers not only meet the demands of professionalism, but also maintain public trust in the integrity and quality of the education they provide.